COORDINATION IN SUPPLY CHAIN IN THE USE OF RAW MATERIAL ALLUMUNIUM SHEET FOR LOGISTIC DIVISION INDONESIAN AEROSPACE (The Indonesian Journal of Business Administration, 2019)
PT. Dirgantara Indonesia is one of the state-owned companies engaged in the design, development and manufacture of airplanes, established since 1976 until now has produced various types of aircraft both civilian aircraft to military aircraft. The background of this research is the accumulation of stock in SAP because there are remnant size due to demand from production, the request is in the form of a request to cut material in a certain size from its standard size of 1220 x 3660 mm, where the size is part of the configuration plan. The results of cutting the material produce remnant where the material size is no longer standard. With coordination in the supply chain in the use of aluminum raw materials in the logistics division can be proposed alternatives to assist in overcoming the remnant, of course this involves various functions and parts within the company. The alternative is the maximum use of one standard allumunium size and the use of a billet size or size that has been adjusted to the production demand. But to achieve this, five implementation plans are needed, which is preparation, alternatives review,  business process set up, role model plan and go live.Keywords: Billet, Remnant, Work Order, Standard Size